Desenvolvimento de novos compostos de borracha natural a partir da desvulcanização em extrusora com rosca dupla - Barbosa, Rafael (2017)
The present study investigated the utilization efficiency of an intermeshing co-rotating twin-screw extruder (ICTSE) in the devulcanization of natural rubber compounds (NR), evaluating the physical, chemical and mechanical characteristics of these materials in each project step. Three accelerated compounds with different sulfur concentrations were submitted to torque rheometry and vulcanized according these results aiming the achievement of elastomers with different crosslinks densities. The influences on the characteristics of the devulcanized material caused by the variation of the extruder barrel temperature, screw rotation, thermoplastics addition and material stiffness were evaluated. Thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), infrared spectroscopy (FTIR), soluble fraction extraction and crosslink density were performed, evaluating the devulcanized compound. Horikx's theory was also used as an indicator of selective crosslink cleavage, defining the compounds to be revulcanized for comparison with the virgin pure material. The revulcanization was carried out with the mixture of the devulcanized compound with the pure, in the proportions of 30/70 w/w, respectively, and in the devulcanized compound singularly, with addition of complementary vulcanization system in both cases. The mechanical, dynamic-mechanical and crosslink density properties of the revulcanized compounds were characterized and evaluated in relation to the properties of the pure compounds. The increase in the concentration of uncrosslinked BN chains and the concentration of sulfur compounds in the extruded samples was observed by thermal tests and spectrocopy, together with the verification of a high level of devulcanization percentage, according to Flory-Rehner, evidencing the regeneration of the natural rubber existent. Also, satisfactory mechanical properties were found in the revulcanized compounds, especially when using auxiliary thermoplastics, revealing the great potential of ERDCI processing for the reuse of discarded BN compounds.